Investigating Boerhavia Diffusa: Phytochemical Analysis and Antioxidant Potential of Methanol, Ethyl Acetate, and Hexane Extracts - Devi P, Shyamala; Shobana, Chandrasekar; Rohini, Durairaj; Usharani, Boopathy; Shamroy R, Phillips (Journal of Neonatal Surgery, 2025)
Boerhavia diffusa, colloquially referred to as punarnava, is a perennial herb indigenous to tropical and subtropical regions, esteemed for its profound medicinal properties, particularly within the context of Ayurvedic practices. Renowned for its anti-inflammatory, diuretic, hepatoprotective, and antioxidant effects, this plant harbors bioactive constituents such as alkaloids, flavonoids, glycosides, and steroids, all of which contribute to its therapeutic efficacy in addressing ailments such as edema, liver dysfunction, renal disorders, and metabolic imbalances. Contemporary pharmacological investigations lend credence to its traditional uses, indicating its potential in the management of conditions like hypertension, diabetes, and rheumatoid arthritis. This study provides an in-depth examination of the plant’s botanical characteristics, phytochemical constituents, and pharmacological activities, underscoring its therapeutic promise while advocating for further clinical exploration. The research delves into the phytochemical profile and antioxidant potential of Boerhavia diffusa through the analysis of methanol, ethyl acetate, and hexane extracts. Phytochemical screening revealed the presence of alkaloids, flavonoids, glycosides, saponins, and steroids across all extracts, with variable concentrations contingent upon the solvent employed. Antioxidant activity was assessed via in vitro assays, including the DPPH assay, which demonstrated considerable antioxidant potential in the methanol and ethyl acetate extracts. These extracts exhibited superior antioxidant activity, suggesting a correlation between polyphenolic compounds and enhanced antioxidant efficacy. Conversely, the hexane extract displayed moderate activity, primarily attributed to the presence of non-polar compounds. The results underscore Boerhavia diffusa as a promising natural source of antioxidants with potential applications in functional foods and therapeutic agents. Nevertheless, additional research is essential to elucidate the molecular mechanisms underlying its antioxidant properties and to evaluate its clinical viability, thereby confirming its safety and therapeutic efficacy in contemporary medical practice